Hydropower projects and environmental licensing process: how different countries manages the problem (Research, Society and Development, 2022)
This research seeks to establish a comparative study among selected countries (Brazil, United States, Canada, Chile and Portugal), regarding aspects of the environmental licensing process for hydroelectric projects. The previous studies consider the Brazilian environmental licensing process to be very complex and differentiated from the other selected countries. There is also a lack of homogeneity among the countries surveyed. In general, environmental licensing is considered a "bottleneck" for the Brazilian electricity sector. With this analysis, it was intended to verify what types of procedures exist in other countries and that could be adopted by Brazil, in order to improve the environmental licensing process of hydroelectric plants. Thus, according to the experience of the countries analyzed, Brazil could improve relations with indigenous peoples and establish a maximum period for finalizing the licensing of hydroelectric plants. Comparative international experiences are important for possible adjustments in the Brazilian licensing process, however, one must not confuse the bureaucracy of the process with excessive simplification.